Deep Grief and Recovery in Anne Enright’s The Gathering - Tika Tri Yolanda; Rika Handayani (English Department, Faculty of Humanities, Andalas University, 2017)
This research aims to present the results of the analysis in Anne Enright’s The Gathering by using psychoanalytical criticism. The focus of the analysis is the psychological problem that experienced by the main female character in this novel, Veronica Hegarty, who presumably gets the difficulty in accepting her lovely brother’s death. This research uses the psychoanalytical theory of Sigmund Freud’s the unconscious, which leads to the another theory that is Prolonged Grief Disorder by Prigerson et al. This research has two results. Firstly, Veronica Hegarty is experienced Prolonged Grief Disorder which can be seen in her deep grief that causes the duration and the intensity of her grief is heightened. Secondly, the writer concludes that Veronica Hegarty tries to cope with her grief by recalling the memories about her brother. From those memories, Veronica realizes her mistakes she has done to him and self-forgiving herself to deal with it. By forgiving herself, she can cope with her grief and she later has the desire to continue her life again.